2012
DOI: 10.1007/s10654-012-9672-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake and risk of open-angle glaucoma: the Rotterdam Study

Abstract: Open-angle glaucoma (OAG) is the commonest cause of irreversible blindness worldwide. Apart from an increased intraocular pressure (IOP), oxidative stress and an impaired ocular blood flow are supposed to contribute to OAG. The aim of this study was to determine whether the dietary intake of nutrients that either have anti-oxidative properties (carotenoids, vitamins, and flavonoids) or influence the blood flow (omega fatty acids and magnesium) is associated with incident OAG. We investigated this in a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 40 publications
2
99
1
5
Order By: Relevance
“…; Ramdas et al. ). However, one study reported a protective effect of alpha‐carotene on glaucoma (≥400 vs. <200 μ g OR [95% CI]: 0.45 [0.23–0.88]; p‐trend=0.021), but not for other carotenoids (Giaconi et al.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…; Ramdas et al. ). However, one study reported a protective effect of alpha‐carotene on glaucoma (≥400 vs. <200 μ g OR [95% CI]: 0.45 [0.23–0.88]; p‐trend=0.021), but not for other carotenoids (Giaconi et al.…”
Section: Resultsmentioning
confidence: 98%
“…However, no significant association between dietary calcium intake and OAG was found (Ramdas et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyruvate dehydrogenase (lipoamide) beta ( PBHB ), responsible for converting pyruvate to a thiamine precursor, was significantly associated ( p < 0.001) with NPG providing support for a role of thiamine biosynthesis in optic nerve degeneration in glaucoma. Vitamin B1 (Thiamine) intake has also been shown to be associated with a reduced risk of POAG (Ramdas et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Higher dietary intake of fruits and vegetables rich in carotenoids (46, 58) has been associated with lower glaucoma occurrence in two observational studies, but two other studies did not find an association (85, 150). Interindividual variability in the absorption and retinal capture of L and Z is high and may explain the lack of associations with dietary intake.…”
Section: Roles In Visual Healthmentioning
confidence: 96%